The Concept of Resolving Medical Crimes Based on a Restorative Justice Perspective in the Criminal Justice System in Indonesia - Azhali Siregar, Mhd (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Medical crimes are a complex issue in the criminal justice system in Indonesia. The concept of resolving medical crimes needs to be seen from a Restorative Justice perspective to create a more holistic and fair approach. Restorative Justice emphasizes the restoration of damaged relationships, not just punishment of the perpetrator. In this context, this research explores the application of Restorative Justice principles in resolving medical crimes. This research uses normative and empirical legal research methods to analyze the development and implementation of Restorative Justice in handling medical crimes in Indonesia. Findings indicate the need for reform in the criminal justice system to integrate Restorative Justice approaches. Implementation of this concept can improve justice, victim satisfaction, and rehabilitation of perpetrators of medical crimes. The results of this research are expected to contribute to further understanding of the effectiveness of Restorative Justice in dealing with medical crimes in Indonesia. The practical implication is the need to improve regulations and increase awareness of actors in the criminal justice system to ensure that justice and recovery are the main focus in handling medical crimes.